Different methods of winning, losing, and training in combat sports and their relationship with overall competitive winningness - Barley, O. R.; Harms, C. A. (Translational Sports Medicine, 2024)
This study aimed to investigate how overall competitive winningness in combat sports depended on patterns of victory and loss, as well as training habits. Competitors (N = 280) from several combat sports participated in the study. The online survey included questions on self-reported patterns of victory (and loss), training habits, general demographics (e.g., age), and sport-specific information (e.g., stage of career and competitive style). Overall, it was found across four models that reflected diversity of winningness in combat sports that the most important predictors of competitive winningness were loss by points (negative), loss by submission (negative), loss (negative) or victory (positive) by throw or technical fall, and loss (negative) or victory (positive) by knockout. The findings applied to amateur and regional/state athletes, and rarely to karate or tae kwon do. Findings around demographics or training habits were largely unremarkable, outside of a relationship between higher training loads and less career winning in wrestlers. Results show that while winning via a finishing sequence (e.g., knockout or submission) is preferable to the judge`s decision or points, the matter of victory is less important than the methods by which an athlete loses. In grappling-only sports, we observed a trend that more losses via finishing sequence were worse for careers than losing by points. In fact, having most of one`s losses coming via judge`s decision or points was beneficial in wrestling and judo, perhaps due to athletes taking less risks and having better defence. These findings may aid practitioners developing effective tactics and training programs.